Consider the following function f(x)=sqrt(x+5) and g(x)=(x-4)/3

odenut6b 2022-09-25 Answered
Consider the following function
f ( x ) = x + 5  and  g ( x ) = x 4 3
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Mackenzie Lutz
Answered 2022-09-26 Author has 13 answers
Solution
Given: f ( x ) = x + 5  and  g ( x ) = x 4 3 ( g f ) x = g ( f ( x ) )
Replace x f ( x )  in  g ( x ) g ( f ( x ) ) = f ( x ) 4 3
Put f ( x ) = x + 5 in g(x)
g ( f ( x ) ) = x + 5 4 3
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more